Lumbar Decompression and Interbody Fusion Improves Gait Performance, Pain, and Psychosocial Factors of Patients With Degenerative Lumbar Spondylolisthesis. Issue 4 (May 2021) - Haddas, Ram; Sandu, Cezar D.; Mar, Damon; Block, Andrew; Lieberman, Isador
Study Design: Prospective cohort study. Objective: Evaluate changes in gait, pain, and psychosocial factors among degenerative lumbar spondylolisthesis (DLS) patients before and 3 months after surgical intervention. Methods: Forty-four symptomatic DLS patients performed clinical gait analysis 1 week before surgery and 3 months after surgery. Patients performed a series of over-ground gait trials at a self-selected speed. Twenty-two matched asymptomatic controls underwent the same battery of tests. Three-dimensional motion tracking was used to analyze gait kinematics. Patient-reported outcomes, gait range of motion, and spatiotemporal parameters compared before and after lumbar decompression with fusion. Results: Surgical intervention resulted in significant improvements in walking speed ( P = .021), stride time ( P = .020), step time ( P = .014), and single-support time ( P = .038). Significant improvements in joint range-of-motion were found for knee ( P = .002) and hip flexion ( P = .006). Degenerative lumbar spondylolisthesis patients reported significant reductions in pain, disability, and improved psychological perceptions for fear-avoidance of pain and motion (all P < .001). Conclusions: Surgical treatment of DLS resulted in a faster, more efficient gait in addition to significant reductions in pain, disability, and psychological fear associated with pain and motion. These beneficial changes that we identified early in the postoperative period indicate that patients return to the quality of life they seek early on. Clinical gait analysis provides objective, quantifiable measures of gait parameters that provide new insight into both the preoperative disability associated with DLS and into the early postoperative function of patients during their rehabilitation.